Television dramatic dialogue a sociolinguistic study - Richardson, Kay, 1955- (New York ; Oxford : Oxford University Press, 2010)
When we watch and listen to actors speaking lines that have been written by someone else the illusion of 'people talking' is strong. 'Television Dramatic Dialogue' examines, from an applied sociolinguistic perspective, and with reference to television, the particular kind of artificial talk that we know as dialogue.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Television broadcasting -- Language; Television series -- Great Britain; Television series -- United States; English language -- Usage; Dialogue analysis; Sociolinguistics